Videoconferencing psychotherapy from a psychodynamic point of view. A qualitative analysis - Laczkovics, Clarissa; Blüml, Victor; Kapusta, Nestor; Hoffmann-Lamplmair, Doris; Casini, Erica; Bazan, Maria; Torres, Miguel Angel Gonzalez; Lendvay, Judit; Normandin, Lina; Nowacki, Henryk; Snigur, Vladimir; Doering, Stephan; et al. (Frontiers in Psychiatry, 2023)
There is a growing interest in delivering videoconferencing psychotherapy (VCP) due to the enormous impact of the COVID-19 pandemic on our lives since the beginning of severe restrictions worldwide in March 2020. Scientific literature has provided interesting results about the transition to remote sessions and its implications, considering different psychotherapy orientations. Less is known about whether and how VCP affects psychodynamic psychotherapeutic approaches and reports on remote work with severe and complex mental health problems such as severe personality disorders are still scarce. The aim of the study was to examine the experiences of psychodynamic psychotherapists, mainly delivering Transference-Focused Psychotherapy (TFP), with the transition and delivery of VCP during the first wave of the COVID-19 pandemic. Four hundred seventy-nine licensed psychotherapists completed an online survey during the peak of the pandemic. Survey data were analyzed using qualitative analysis. Results are presented and discussed concerning advantages and disadvantages regarding the access to psychotherapy, the specificity of the online video setting, bodily aspects, the quality of the therapeutic relationship, the therapeutic process including technical aspects and therapist's experience. Furthermore, we analyzed and discussed the statements concerning transference and countertransference reactions differentiating between high-level borderline and neurotic patients and low-level borderline patients. Our results support the importance to identify patients who potentially benefit from VCP. Further research including more prospective randomized controlled trials are needed to investigate the therapeutic implications of the findings.